Using design theory to bridge Design and Science: understanding innovation and the role of Design when developing novel technologies. - Kentrotis, Konstantinos (Cranfield University, 2019)
The value of design is nowadays largely recognised, especially in its manifestations of design thinking, product and service design, business organisation as well as disruptive innovation. Design in the context of the present study is examined from a different perspective, the one of modern design theory. It is treated as a human activity of generating innovative concepts, regardless of fields of disciplines, in an attempt to identify which are the techniques that enable invention to occur. The study aims at providing a better understanding of design and its cognitive processes, relying on formal design theory and using a real-world design challenge as a case study. The case study corresponds to a global, high-profile project funded by the Bill & Melinda Gates Foundation. Contemporary western-style toilets require a large quantity of clean water and an integrated sewage system to operate, but 2.3 billion people remain without access to improved sanitation. For this part of the globe’s population, a waterless and energy-neutral toilet would constitute a solution with high potential. An important piece of this toilet is a technology which dewaters and dries human faeces so that it can be further processed by the system. At the moment, such a technology with low requirements in terms of size, energy and power demands does not exist. In the context of this research, a novel, patented drying technology was designed and developed. The novel dryer designed and developed in the context of the aforementioned project is represented by using modern design theory. The case study is also used to demonstrate the way that innovative concepts are generated and to identify the design techniques that are crucial to invention process, irrelevant to the field or discipline within which it takes place.
Keywords: Axiomatic design; design theory; drying technology; design process; case study; C-K theory; generativity; innovation; innovative conceptual design